A Model for Mangrove Forest Management Based on Community Empowerment in Bantul Regency - HASTUTI, Tiwuk Kusuma; YULIATI, Umi (Journal of Environmental Management and Tourism, 2018)
Mangrove Forests along the coastal areas of the coastal region contributing to security and provide food as well as building material for the people of the village of mangrove forests. However, the mangrove forest has experienced over the function and suffered damage. Depletion of mangrove ecosystems is becoming a serious concern of developing countries, including Indonesia. These conditions encourage the Government of Bantul Regency to manage mangrove forests through the mangrove forest ecotourism development berbasisis community empowerment so that mangrove forests remain sustainable and able to improve the economy of the community. This is in line with the vision of Governor of Daerah Istimewa Yogyakarta (DIY) South Coast Area who makes as a DIY home page, along the coast as a green belt, tourist destinations and the development of agricultural land sand to food security. This research is a descriptive research using qualitative approach. Research methods using the techniques of observation, interview, Focus Group Discussion (FGD), and the study of the literature. The technique of sampling done by the method of purposive sampling and snowball. The data were analyzed by using interactive methods of analysis and thematic analysis. Data analysis was performed interactively with reviewing all the data, reduction, and checking the validity of the data to produce a framework of analysis that has a frame of meaning while interpreting the data to derive the conclusion. The goals of this research are: formulating models and development strategy of ecotourism community empowerment-based mangrove forests in Bantul Regency.